2012
DOI: 10.1002/hyp.8390
|View full text |Cite
|
Sign up to set email alerts
|

The Fill–Spill Hydrology of Prairie Wetland Complexes during Drought and Deluge

Abstract: Abstract:The fill-spill of surface depressions (wetlands) results in intermittent surface water connectivity between wetlands in the prairie wetland region of North America. Dynamic connectivity between wetlands results in dynamic contributing areas for runoff. However, the effect of fill-spill and the resultant variable or dynamic basin contributing area has largely been disregarded in the hydrological community.Long-term field observations recorded at the St. Denis National Wildlife Area, Saskatchewan, allow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
170
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(177 citation statements)
references
References 28 publications
6
170
0
Order By: Relevance
“…The hydrological complexity of the landscape is also largely influenced by glacial and post-glacial geomorphological processes, which have imparted a tremendous degree of heterogeneity. Morainal deposits, comprised of a variable mix of soil textures, are often topographically indeterminate and consist of areas which are internally drained and infrequently contribute to stream flow (Zebarth and de Jong, 1989;Shaw et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The hydrological complexity of the landscape is also largely influenced by glacial and post-glacial geomorphological processes, which have imparted a tremendous degree of heterogeneity. Morainal deposits, comprised of a variable mix of soil textures, are often topographically indeterminate and consist of areas which are internally drained and infrequently contribute to stream flow (Zebarth and de Jong, 1989;Shaw et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Hydrological processes in the region are complex and unusual, characterized by closed basins isolated from any regional drainage network, with drainage via a spill and fill sequence into terminal ponds (Shook and Pomeroy, 2011). Snowmelt runoff from surrounding uplands and precipitation on the wetlands are the dominant hydrological inputs into the wetland systems, together with occasional runoff events due to high-intensity rainfall, whereas snow distribution over the landscape is an important control on the hydrology (Shaw et al, 2012;Spence and Woo, 2003); semi-arid conditions result in minimal shallow groundwater recharge from uplands, while ponds drain to shallow groundwater beneath the depressions (van der Kamp and Hayashi, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Huang et al (2011a) showed a 600 % increase in total surface-water area in the Cottonwood Lake area between 1982 and 2009. Efforts to understand how surface-water expansion can connect features across the landscape have been restricted to wetland-wetland connections (Leibowitz and Vining 2003;Kahara et al 2009), and connections between wetlands and streams (Huang et al 2011b;Shaw et al 2012;Vanderhoof et al 2015). This study extends previous findings Wetlands connected to a lake under both the saturated and inundated thresholds were assumed to be subsumed, while wetlands connected only under the saturated threshold were assumed to have merged with lake (i.e., were not subsumed).…”
Section: Discussionmentioning
confidence: 99%
“…Intermittent or temporary linear connections (e.g., ephemeral channels, swales, ditches, fill-and-spill events) that connect some waters (Shaw et al 2012) are difficult to detect with Landsat and often are not well documented by NHD, which has been shown to inconsistently map such features (Lang et al 2012;Fritz et al 2013). Although finer spatial resolution imagery may expand the types of connectivity captured, these data sources are often collected on-demand, reducing our ability to capture a wide range of climate conditions.…”
Section: Landscape and Lake-scale Analysismentioning
confidence: 99%